Identificação de proteínas antigênicas e diferencialmente abundantes em Leishmania (Leishmania) amazonensis, L. (Viannia) braziliensis e L. (L.) infantum - Bruna Soares de Souza Lima Rodrigues (2017)
Leishmaniasis are disease with a wide diversity of clinical forms, due to the different species. The cutaneous leishmaniasis (LT) is frequently associated with Leishmania (Leishmania) amazonensis and / or L. (Viannia) braziliensis infection, while the visceral form (LV) is caused by L. (L.) infantum. Proteins are one of the main molecules that determinete the largest number of biological variations. Another relevant aspect is that an efficient diagnosis contributes not only to clinical evaluation, but also to disease epidemiology and control. In the present study, by means of a proteomic approach (DIGE), we identified differentially abundant proteins among the most frequent Leishmania species in our country, L (L.) amazonensis, L. (Viannia) braziliensis and L. (L.) infantum. Through the use of bioinformatics tools, the interactions of these proteins in biological networks, as well as the biological processes in which these molecules act, were shown. In our study we highlight 6 of these functional categories: nitrogen metabolism, stress response, cytoskeletal organization, transport, development of structures and pathways associated with regulation of the immune system; being in the latter the enrichment was present in L. braziliensis and L. infatum, only. Data revealed that L.infatum, species with greater visceral potential, showed higher amount of proteins detected for almost all the processes. In addition, we selected from these proteins which were also antigenic according to the clinical form, TL or VL, of the sera used in the western blot. Antigenic proteins were subjected to in silico analysis for the prediction of B cell epitopes without similarities with orthologs in Trypanosoma cruzi. Among 18 proteins identified with these characteristics (more abundant, specific and antigenic in one species relative the others) eight belongs to species that cause the cutaneous form of the disease (L. amazonensis and L. braziliensis) and 10 belongs to the species that cause the visceral form (L. infantum). The 68 epitopes predicted simultaneously by the ABCPred and BCPreds software in these proteins were synthesized in cellulose membrane and evaluated for reactivity. Considering the analyzed data, we highlight two proteins of L. amazonensis, which have potential for specific diagnosis of TL: metallopeptidase, Clan MA (E) -Familia M3 and a hypothetical protein. Both are more abundant in this species, they have exclusive reactivity to the sera from TL pool and most of the epitopes no show similarity to orthologs in T. cruzi. In addition, nine epitopes from proteins selected by exclusive reactivity of sera from TL patients to L. amazonensis extract were considered as potential antigens for the serological diagnosis of TL in humans.